The chemistry and technology of petroleum - Speight, James G. (Chemical industries., 2014)
This bestselling reference is known for its comprehensive treatment that traces the science of petroleum from its subterranean formation to the physicochemical properties and the production of numerous products and petrochemical intermediates. Presenting nearly 40 percent new material, the fifth edition includes more coverage of offshore oil and gas and presents issues related to economics and future refineries as well as the changing character of the refinery feedstock. Also, environmental issues as they relate to the laws are given more detailed coverage. Existing material is updated and.